2016
DOI: 10.1016/j.ibiod.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of wood colonized by Gloeophyllum trabeum

Abstract: a b s t r a c tThis paper examines how wood decay fungi affect the electrical resistance (resistivity) of wood to determine whether an electrical resistance probe could be deployed as a remote sensor in a wall to detect wood decay. Electrical resistance measurements were taken on wood blocks exposed to Gloeophyllum trabeum in a standard soil bottle tests (AWPA E10) as a function of time. To understand how and why resistance changed with time, results were compared against resistance measurements taken in steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(19 reference statements)
0
11
0
1
Order By: Relevance
“…In the soil block tests, the moisture content of the wood specimen would also depend on moisture generation from the breakdown of wood polymers by the fungus and active water translocation by the Forests 2020, 11, 299 3 of 10 fungus. It has been shown that for untreated wood in the standard soil block tests, the wood moisture content increases during the first 3 weeks of the decay test and then levels off in an optimal range for fungal growth [17]. Measurements of this type are lacking for acetylated wood.…”
Section: Introductionmentioning
confidence: 99%
“…In the soil block tests, the moisture content of the wood specimen would also depend on moisture generation from the breakdown of wood polymers by the fungus and active water translocation by the Forests 2020, 11, 299 3 of 10 fungus. It has been shown that for untreated wood in the standard soil block tests, the wood moisture content increases during the first 3 weeks of the decay test and then levels off in an optimal range for fungal growth [17]. Measurements of this type are lacking for acetylated wood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the trend in the electrical resistance versus the ML is contrary to the findings of Kirker et al (2016). They found that the electrical resistance of wood significantly D r a f t decreased with the increase in the ML until approximately 10% ML.…”
Section: Discussionmentioning
confidence: 70%
“…when wood starts to decay after the fungal attack. Because the resistance was not sensitive to the change in the MC and became constant when the MC was greater than 30% in sound wood (Kirker et al 2016;Gao et al 2018), the decrease in resistance cannot be attributed to the increase in the MC of decayed wood. Furthermore, as the electrical resistance exhibited a decreasing trend throughout the decay period from 4 to 24 weeks, the decrease in the resistance cannot simply be attributed to the increase in the MC of decaying wood but may significantly depend on the changes in the cation concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moisture Content (MC) in wood affects its physical and mechanical properties [1][2][3][4]. Additionally, a high MC value above the fiber saturation point (roughly 30% MC) maintained over time increases the risk of infestation and decay of wooden substrate by wood-destroying fungi [5].…”
Section: Introductionmentioning
confidence: 99%